2010
DOI: 10.1016/j.cell.2009.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Kinase-Dead BRAF and Oncogenic RAS Cooperate to Drive Tumor Progression through CRAF

Abstract: SummaryWe describe a mechanism of tumorigenesis mediated by kinase-dead BRAF in the presence of oncogenic RAS. We show that drugs that selectively inhibit BRAF drive RAS-dependent BRAF binding to CRAF, CRAF activation, and MEK–ERK signaling. This does not occur when oncogenic BRAF is inhibited, demonstrating that BRAF inhibition per se does not drive pathway activation; it only occurs when BRAF is inhibited in the presence of oncogenic RAS. Kinase-dead BRAF mimics the effects of the BRAF-selective drugs and ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

89
1,259
4
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,325 publications
(1,359 citation statements)
references
References 34 publications
89
1,259
4
7
Order By: Relevance
“…For example, the finding that approximately 50% of melanomas harbour oncogenic BRAF mutations has driven drug discovery programmes that have generated potent, selective inhibitors that are active against V600E BRAF mutant tumor cells (25)(26)(27). These agents have yielded dramatic results in clinical trials in patients with V600E BRAF mutant melanoma (28,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the finding that approximately 50% of melanomas harbour oncogenic BRAF mutations has driven drug discovery programmes that have generated potent, selective inhibitors that are active against V600E BRAF mutant tumor cells (25)(26)(27). These agents have yielded dramatic results in clinical trials in patients with V600E BRAF mutant melanoma (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…These observations highlight the need for continued research effort in to novel therapies for BRAF mutant melanoma. As a note of caution, however, the importance of a detailed understanding of the molecular pathology of MMM was underlined in preclinical work that showed that, in BRAF wild-type tumor cells, the use of a BRAF inhibitor can activate signalling through BRAF-CRAF dimerisation and, as a result, may accelerate tumor growth (27). Therefore, future development of specific targeted therapies for MMM must include a detailed analysis of the various genetic backgrounds of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…This work was essential in identifying MEK as being of particular importance in BRAF-inhibitor resistance and, thus, the potential synergy between BRAF and MEK inhibitors 55 . The mechanistic specificity of this work additionally led to the description of a phenomenon dubbed 'paradoxical activation' of the MAPK pathway via BRAF inhibition in BRAF-wild-type cells, for example, keratinocytes [56][57][58][59] . This discovery suggested that some of the hyperproliferative cutaneous manifestations associated with BRAF inhibition in the clinic might be mitigated by combination therapy incorporating a MEK inhibitor.…”
Section: Braf-targeted Therapiesmentioning
confidence: 99%
“…Furthermore, as this inhibitor is only effective on cells transformed by this V600E mutation, another BRaf-specific inhibitor, GSK2118436, which targets the V600K mutation, is also in a small phase III trial having shown great potential in patients with brain metastases 81 . However some caution remains as the inhibition of the BRaf mutation V600E (and also V600K by GSK2118436) with these BRaf inhibitors has been shown in some patients to reactivate the MAPK pathway through CRaf 82,83 , and developing resistance to BRaf inhibitors is a problem.…”
Section: Current Therapies In the Treatment Of Metastatic Melanomamentioning
confidence: 99%